Schindleria elongata, a new species of paedomorphic gobioid from the Red Sea (Teleostei: Schindleriidae). Issue 5 (14th February 2017) - Fricke, R.; Abu El‐Regal, M.
Abstract : A new species of paedomorphic gobioid, Schindleria elongata, from the Red Sea, is described on the basis of five specimens. The new species is characterized by its lack of body pigmentation; the body depth at pectoral‐fin origin 4–5% of standard length ( L S ) and at anal‐fin origin 5–7% L S ; the predorsal length 66–70% L S ; pre‐anal length 66–71% L S ; dorsal‐fin rays 13 or 14; anal‐fin rays 10 or 11; first dorsal‐fin ray at myomere 20 or 21; first anal‐fin ray below second to fourth dorsal‐fin rays; myomeres 19 or 20 + 13 or 14 = 33 or 34 total; premaxillae and dentaries with small teeth; gas bladder located posteriorly at 56–60% L S ; males with a rod‐like, flexible urogenital papilla lacking lobes, projections or accessory papillae, with distal half tapering to a broad, angular point and usually posteriorly directed. A key to the species of Schindleriidae is presented.